Permainan Tradisional Pada Pembelajaran Kosakata Bahasa Inggris di SDN BANJAREJO 01 - Siti Mafulah (Jurnal VOK@SINDO, 2015)
The purpose of this research is to describe the use of traditional games which were integrated with English teaching learning at primary school level. Descriptive qualitative was used in this research through interview, observation, documentation and questionnaire. The finding showed that 85% of students love this teaching model. Due to the implementation of traditional games in teaching learning process, students easily remembered the vocabulary given whether in spoken and written forms. The games given were kelereng (marbels), ular naga, congklak and engklek. Students did not find any difficulties in doing the games because all students were familiar with them as their daily games. In addition, the students improved their language function and they were not shy to use simple English conversation and instructions. The vocabularies given were based on their daily life such as name of the day, name of the month, shapes, colors, animals and so on. Students were motivated and enthusiastic in learning English vocabulary. As conclusion, modified traditional games are useful for primary school level in teaching vocabulary